The teacher and his work - Chaffee, Spencer Norman (My University, 1891)
Introduction: The work of the teacher with historic man. In India he gathered the boys about him in the shade of trees or under sheds, and with a discipline enforced by the appreciation of cold water and the sod, instructed them in accordance with the requirements of the caste to which they belonged. Among the Israelites the early instructors were the parents; and, until the time of Christ, the pedagogue was unknown, but with the establishment of schools in the year 64, began out of the brightest educational system; and the teachers styled “the true guardians of the city”, were expected to possess the highest virtues, and were respected above all other persons.
Citation: Chaffee, Spencer Norman. The teacher and his work. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Education; Teacher; BCE; India; Israelites; Theses; Manuscripts (documents)